Basophilic stippling in red blood cells in the bone marrow: indication for lead poisoning diagnosis. Issue 2 (February 2022) - Kano, Nagamasa; Fukui, Sayato; Kushiro, Seiko; Inui, Akihiro; Saita, Mizue; Kura, Yoshimasa; Sawada, Umihiko; Naito, Toshio
A 40-year-old man presented at our hospital with anaemia that had been undiagnosed for 2 years. Blood tests, endoscopy, and contrast-enhanced computed tomography were performed, but a definitive diagnosis could not be made. A subsequent bone marrow biopsy revealed basophilic stippling in transformed red blood cells, which led to a differential diagnosis of lead poisoning. Additional tests revealed elevated levels of lead in the blood. Basophilic stippling is generally found on a peripheral blood smear in lead poisoning patients; however, in this case, basophilic stippling was found only on the bone marrow smear and not in the blood smear. Even if basophilic stippling is not found in the peripheral blood, lead poisoning cannot be excluded.